The quest for seafloor macrolitter: a critical review of background knowledge, current methods and future prospects - Canals, M; Woodall, L (IOP Publishing, 2021)
The seafloor covers some 70% of the Earth's surface and has been recognized as a major sink for marine litter. Still, litter on the seafloor is the least investigated fraction of marine litter, which is not surprising as most of it lies in the deep sea, i.e. the least explored ecosystem. Although marine litter is considered a major threat for the oceans, monitoring frameworks are still being set up. This paper reviews current knowledge and methods, identifies existing needs, and points to future developments that are required to address the estimation of seafloor macrolitter. It provides background knowledge and conveys the views and thoughts of scientific experts on seafloor marine litter offering a review of monitoring and ocean modeling techniques. Knowledge gaps that need to be tackled, data needs for modeling, and data comparability and harmonization are also discussed. In addition, it shows how research on seafloor macrolitter can inform international protection and conservation frameworks to prioritize efforts and measures against marine litter and its deleterious impacts.